Learning Fatigue in Online Education: Analysis of Students' Cognitive Saturation in the Digital Era - David Darwin (Ludi Litterarri, 2026)
Learning fatigue, or learning saturation, in the context of online education is a phenomenon that is increasingly receiving serious attention among educational researchers and practitioners. This article presents a systematic review of recent studies on student cognitive fatigue in online learning in the digital era, analyzing its causal factors, impacts on achievement and mental health, and effective intervention strategies. The review integrates findings from more than twenty international studies published between 2021 and 2025. The analysis shows that cognitive overload, prolonged screen exposure, and minimal social interaction are the three main factors causing learning fatigue. The prevalence of screen fatigue was the highest, reaching 61.3% in the high category, followed by online concentration disorders at 57.2%. The most significant impacts include decreased learning motivation, academic burnout, and mental health disorders. Intervention strategies that have proven effective include the application of active learning methodologies, digital wellness frameworks, and the use of artificial intelligence for real-time cognitive-emotional state detection. The implications of these findings are relevant for online curriculum developers, higher education institutions, and policymakers in designing sustainable digital learning ecosystems